Propyl gallate metal complexes: Circular dichroism, BSA-binding, antioxidant and cytotoxic activity. (17th June 2017) - Massoni, Murilo; Clavijo, Juan C. Tenorio; Colina-Vegas, Legna; Villarreal, Wilmer; Dias, Julia S.M.; da Silva, Guilherme A.F.; Ionta, Marisa; Soares, Marisi; Ellena, Javier; Dorigueto, Antônio C.; Barbosa, Marília I.F.; Batista, Alzir A.
Graphical abstract: The propyl galate (PG) complexes [Pt(PG)(PPh3 )2 ] and [Ru(PG)(dppm)2 ] were synthesized and characterized and their anticancer activities were evaluated. The results showed that the [Ru(PG)(dppm)2 ] complex is more active, when compared to the free propyl galate molecule and to the platinum complex. The complexes interact with BSA mainly by van der Waals force or by hydrogen bonds. It was observed that the [Pt(PG)(PPh3 )2 ] complex has an inhibitory effect against free radicals, whereas the [Ru(PG)(dppm)2 ] is not active. Abstract: Herein syntheses and characterization of the complexes [Pt(PG)(PPh3 )2 ] (1 ) and [Ru(PG)(dppm)2 ] (2 ), where PG (propyl gallate) = propyl 3, 4, 5-trihydroxybenzoate, PPh3  = triphenylphosphine and dppm = 1, 1-bis(diphenylphosphino) methane, are described. The structure of the complex [Pt(PG)(PPh3 )2 ] was elucidated by X-ray diffraction. The cytotoxicity of the complexes against four tumor cell lines, lung carcinoma (A549), breast carcinoma (MCF-7), hepatocellular carcinoma (HepG2), glioblastoma (U251MG), and a normal fibroblast (CCD-1059Sk) were evaluated. The selectivity index values showed that complex (2 ) is more potent and selective than the free propyl gallate molecule and complex (1 ). Furthermore, complex (2 ) is a slightly higher active against the tumor cells MCF-7 and HepG2 than the cisplatin. In addition, BSA-binding experiments and antioxidant activity of the complexes were evaluated. The interactions of the complexes with the BSA showed negative Δ H and Δ S values, leading to van der Waals force or hydrogen bond formation between the complexes and the biomolecule. Furthermore, the negative Δ G values reveal that the interaction process of complex/BSA is spontaneous. It was observed that the [Pt(PG)(PPh3 )2 ] complex has an inhibitory effect against free radicals, whereas [Ru(PG)(dppm)2 ] was not active. Circular dichroism showed that the free ligand and the complexes are unable to modify the DNA secondary structure of this biomolecule.